PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN UNTUK MENGEMBANGKAN POTENSI PESERTA DIDIK DI MI NAILUL HUDA JIMBARAN-BADUNG, BALI - Katmani; Sudarsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the practices and impact of a humanistic approach in learning to develop the potential of students at MI Nailul Huda, Jimbaran-Badung. The humanistic approach, which emphasizes respect for the individual, is considered relevant to the principles of Islamic education. This qualitative research utilized a Focus Group Discussion (FGD) method with five teachers from MI Nailul Huda serving as subjects. The data were analyzed thematically to identify the understanding, practices, and impact of this approach. The findings indicate that the implementation of the humanistic approach successfully created a positive learning environment, strengthened teacher-student interpersonal relationships, and significantly enhanced students' self-confidence, creativity, and empathy. The study found that this approach aligns with the concept of fitrah (human nature) in Islam and the educational vision proposed by al-Ghazali. However, challenges such as a dense curriculum and cognitive-oriented assessment remain major obstacles. The research recommends continuous training to strengthen the consistent implementation of this approach.